Foreign Investments in Disputed Maritime Zones: Maritime Disputes as Events of Force Majeure in International Law and International Investment Contracts - Kassem, Hazem (BAU Journal - Journal of Legal Studies, 2020)
Sovereign rights in Exclusive economic zones and Continental shelves are functionally limited to the economic exploitation of these zones. Moreover, in the case of disputed maritime zones these sovereign rights are neither exclusive nor necessarily constant. Nevertheless, states are still expected to provide the investments established in these zones the same treatment they should provide in their territories where they exercise full and constant sovereignty. If a host state agrees to the establishment of an investment in a maritime zone that become later contested, do the occurrence of the contestation and the hazards arising from such contestation relief the host state from its contractual and treaty obligations toward the investment by virtue of the force majeure concept. This paper argues that a traditional interpretation of the force majeure concept in respect of investment agreements and contracts, hampers states ability to de-escalate their maritime disputes, diminishes its capacity to conclude delimitation agreements and reduces the promotion of the UNCLOS III as well as its mechanisms for disputes settlement. It proposes a contextualist interpretation of the force majeure concept that is adapted to the exploitation of disputed maritime zones and states obligations under the international law of the sea. First, it examines the concept of force majeure as a doc-trinal hypothesis and its applications in international contracts and international in-vestment agreements. Second, it analyzes the legal act of maritime contestation as a force majeure event according to the possible interpretations of the concept of “force majeure”. Finally, it examines the recurrent legal implications susceptible of arising out of a contestation; provisional orders and unfavorable delimitation and their qualifica-tion as a force majeure event in the realm of investment agreements and contract.
Keywords: BIT; Disputed maritime zones; Force majeure; Foreign investment; Investment contracts; Maritime contestation; Maritime delimitation; Provisional measures

La portée de la conciliation préalable en matière de procédures simplifiées de recouvrement de l'OHADA dans la réalisation des droits du créancier - Tonda, Franck (International Multilingual Journal of Science and Technology, 2020)
Keywords: Conciliation; Créancier; MARD; Procédure simplifiée; Recouvrement de créances

L'arbitrage international et les contrats de transfert de technologie en droit comparé : France, Syrie, Égypte - Al Youssef, Omar (Aix-Marseille Université, 2020)
La France en tant qu’un pays développé possède une richesse juridique et judiciaire à propos de l’arbitrage et des contrats de transfert de technologie. Alors que la Syrie n’a pas jusqu’à ce moment un système juridique spécial à ces contrats. En plus, la loi syrienne de 2008 sur l’arbitrage a besoin d’être modifiée en raison des erreurs juridiques massives commises dans cette loi. S’agissant de l’Égypte, la loi de 1999 sur le commerce a mis en place un système juridique solide pour régir les contrats de transfert de technologie et l’arbitrage. Il faut mentionner que la jurisprudence égyptienne est très développée par rapport à la jurisprudence syrienne, ce qui me permet de faire une comparaison entre la France et les deux pays en développement. France as a developed country has a wealth of legal and judicial matters relating to arbitration and technology transfer contracts. While Syria does not yet have a special legal system for these contracts. In addition, Syria's 2008 arbitration law needs to be amended due to massive legal errors in that law. In Egypt, the 1999 trade law established a strong legal system to govern technology transfer contracts and arbitration. It should be mentioned that Egyptian case law is very developed compared to Syrian case law, which allows me to make a comparison between France and the two developing countries.
Keywords: Approche comparée; Arbitrage; Arbitrage international; Arbitragem; Arbitration; France; Syrie; Transfert de technologie; Égypte; Étude comparative

Limites da jurisdição e das decisões jurisdicionais estatais no âmbito da internet - Laux, Francisco de Mesquita (Universidade de São Paulo, 2020)
A tese tem como objetivo desenvolver as relações entre o exercício da jurisdição - especialmente, a limitação territorial de eficácia das decisões - e os conflitos vinculados à postagem de manifestações infringentes na internet. A hipótese central defendida pela tese é a de que a jurisdição e as decisões judiciais estatais, quando direcionadas a remover postagens na internet, têm seu espectro de eficácia limitado ao território do Estado em que proferidas. Isso significa dizer que pessoas que se conectam à internet a partir de outros Estados não podem ser diretamente impactadas pelo comando. A tese busca demonstrar, ainda, que o modelo de reserva de jurisdição estatal não é efetivo, independentemente de critérios de eficácia territorial, para solução de problemas especialmente vinculados à disseminação em massa de manifestações danosas. A tese foi dividida em três capítulos. No primeiro, o objetivo será o de estabelecer os princípios e regras vinculados às ideias de jurisdição internacional de acordo com a legislação brasileira de direito processual civil e direito internacional privado. Na segunda parte, será a vez de abordar os temas em referência a partir das perspectivas trazidas por ordenamentos jurídicos estrangeiros, especialmente recentes pronunciamentos advindos dos Estados Unidos da América e do Tribunal de Justiça da União Europeia a respeito dos limites territoriais de decisões judiciais destinadas a produzir efeitos na internet, além da apresentar uma breve contextualização de como outros países - como China, Brasil, Argentina e México - encaram fenômenos vinculados ao ambiente virtual. No terceiro e último capítulo, tais soluções serão compatibilizadas de modo a delimitar a amplitude territorial da jurisdição e das decisões jurisdicionais estatais nos casos que envolvem conflitos para retirada de postagens na internet. O capítulo abordará, também, a perspectiva de processos e decisões não estatais, adotados por gestores de redes sociais ou tribunais privados em um ambiente de autorregulação regulada, e de que modo isso pode ter reflexos no direito processual sob a ótica das noções de online dispute resolution (ODR). The thesis aims to reveal the relationship between jurisdiction (more specifically, its territorial scope/range) and the conflicts linked to posting abusive or illegal statements on the internet. The main hypothesis of the thesis is that jurisdiction and decisions rendered by the Judiciary, when directed to remove posts on the internet, have their scope/range limited to the territory of the State in which they are rendered. This means that people who connect to the internet from other States cannot be directly impacted by the decision. The thesis also seeks to demonstrate that the state jurisdiction reserve model is not effective, regardless of territorial effectiveness criteria, for solving problems especially linked to the mass dissemination of harmful manifestations. The thesis was divided into three parts. Part 1 aims to establish the principles and rules linked to the ideas of international jurisdiction in accordance with Brazilian legislation on civil procedural law and private international law. Part 2 discusses the issues in reference from the perspectives brought by foreign legal systems, especially recent pronouncements from the United States of America and the Court of Justice of the European Union regarding the territorial scope/range of judicial decisions aimed at produce effects on the internet, in addition to presenting a brief contextualization of how other countries - such as China, Brazil, Argentina and Mexico - face phenomena linked to the virtual environment. In the third and last part, such solutions will be compared in the objective of delimiting the territorial scope of the jurisdiction and of the state jurisdictional decisions in cases involving conflicts for the removal of posts on the internet. The chapter will also address the perspective of non-state processes and decisions, adopted by managers of social networks or private courts in an environment of "regulated self-regulation", and how this may have an impact on procedural law from the perspective of notions of online dispute resolution (ODR).
Keywords: Argentina; Brasil; Chile; China; Competência territorial; Direito Comparado; Direito Processual; Estados Unidos; Europa; Internet; Jurisdiction; Jurisdição; Jurisdição internacional; MARD; Mediación; Mediation; Mediação; Mediação e conciliação; Médiation; México; Mídias sociais; ODR; Online Dispute Resolution; Regulated selfregulation; Scope of jurisdiction; Social networks; Territory

International Commercial Arbitration - Kizi, Boratova Ziyoda Sobir (International Journal of Trend in Scientific Research and Development, 2020)
This article is devoted to the complex analysis of the English legislation of the international commercial arbitration. The author analyzed the commercial disputes and the bodies that proceed these disputes in England as well as main statutes regulating the international commercial arbitrations of England. The international commercial practices of the London International Court of Arbitration are described. Moreover, the author represents the main conclusions formed on the basis of the provisions of the national legislation on commercial arbitration and the regulations of the most well-known international arbitrations in England.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration Act 1996; Arbitration institution; Commercial disputes; International commercial arbitration; The LCIA Rules; The London International Court of Arbitration (LCIA)

O recurso à arbitragem no âmbito das sociedades comerciais : os conflitos societários internos - Vaz, Juliana Touro Cerejo Rabaça (Universidade Católica Portuguesa, 2020)
A presente dissertação tem como objetivo analisar, à luz do ordenamento jurídico português, a possibilidade e adequação do recurso ao instituto da arbitragem como meio de resolução dos litígios intrassocietários, isto é, os litígios emergentes das relações entre os sócios de uma sociedade, os resultantes das relações entre os sócios e a própria sociedade, ou ainda no âmbito das relações entre os sócios ou a sociedade per si e os titulares dos órgãos de administração ou de fiscalização da mesma. Para tal, foi inicialmente adotada uma perspetiva comparatística com outros ordenamentos jurídicos. Posteriormente, foi adotada uma abordagem expositiva, do instituto da arbitragem em Portugal, analisando inicialmente de um modo geral, especificando depois o propósito principal da presente dissertação – a arbitrabilidade dos litígios intrasocietários, nomeadamente o regime da convenção de arbitragem, do tribunal arbitral e da própria sentença arbitral. Avaliadas as vantagens e os inconvenientes do recurso à arbitragem enquanto meio de resolução alternativa de litígios, e a sua aplicabilidade aos litígios intrassocietários, tomando como referência a escassa regulamentação deste instituto neste domínio no nosso ordenamento jurídico, conclui-se a presente dissertação com uma proposta de regulamentação legal e outra estatutária da arbitragem dos referidos litígios intrasocietários.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Entreprises commerciales; Litige interne

التحكيم رديفاً للقضاء في حل المنازعات - دراسة فقهية - Abu Lail, Mohammad (Jordan Journal of Islamic Studies, 2020)
Arbitration is considered as one of the basic means that has been legislated by Islam to resolve the people's disputes. Usually the resolutions of the arbitration are fast, guarantee the rights, respect the essence of justice and reduce the level of the controversy. Today, arbitration plays a vital role in resolving the international disputes such as the economic, political and local disputes as long as its effect upon the resolution of the internal disputes. This study highlights on the arbitration role in resolving the disputes as along with judiciary through showing the advantages of the arbitration and explain the relationship between arbitration and judiciary. And clarify its areas and its implications in jurisprudence. This study found out that the arbitration has a pivotal role in resolving the disputes resulting from the contractual and non-contractual relationships and the disputes resulting from the people in their natural and moral capacity, both internally as well as externally The study has shown the jurisprudence has taken the lead in explaining the terms and effects of the arbitration.

Le rôle de la confidentialité dans la procédure préventive de conciliation de l’OHADA - Nkouamo Ngnegue, Luc Norbert (International Multilingual Journal of Science and Technology, 2020)
La procédure de conciliation est l’une des innovations de la réforme de l’Acte Uniforme relatif aux procédures collectives d’apurement du passif. Le législateur OHADA l’a institué dans l’objectif de mieux gérer la prévention de la cessation des paiements des entreprises en difficulté financière. La conciliation est entrée dans la sphère des procédures collectives de l’OHADA avec un principe clé à savoir la confidentialité. Le principe de confidentialité constitue une pierre angulaire de la conciliation au regard de la place qu’elle occupe dans le dénouement de celle-ci. Le législateur communautaire fait intervenir ce principe dans tout le dénouement de la conciliation. La confidentialité se présente ainsi comme un aspect phare de la procédure. Cet état de chose nous a alors amené à s’interroger sur le rôle que peut bien jouer cette confidentialité qui anime l’ensemble de la procédure préventive. Selon notre point de vue, la confidentialité joue un double rôle dans la procédure de conciliation. Elle favorise d’une part la protection du débiteur soumis à la procédure en lui assurant la préservation de son crédit ainsi que les informations divulguées et d’autre part, facilite l’efficacité de la procédure à travers son imposition générale même si elle est un peu fragilisée par certaines atteintes. The procedure of conciliation is an innovation of the uniform Act organizing the legal treatement enterprises difficulties. The OHADA lagislator has institute it with the objective for the better manage in the suspension of payments prevention for enterprises in financial difficulty. The conciliation procedure has come in the sphere of OHADA legal treatement enterprises difficulties with a main principle which is confidentiality. The principle of confidentiality constitute a cornerstone of the conciliation procedure ending according to the Sport place it occupe. The Community legislator makes this principle to intervene in all the conciliation procedure. The confidentiality is present as a main aspect of the procedure. This situation brought us to question the role of the confidentiality witch lead all the preventive procedure. According to our point of view, the confidentiality plays a double role in the conciliation procedure. It favours firstly the protection of the debtor submit to the procedure insuring the preservation of his credit as well as divulgates informations and secondly, it facilitate the effectiveness of the procedure by his general using even it is fragilize by certains attacks.
Keywords: Cessation des paiements; Conciliation; Confidentiality; Confidentialité; Debtor protection; Efficacité de la procédure; Procedure effectiveness; Protection du débiteur; Suspension of payments

The Changing Paradigm of International Tax Dispute Settlement: What Are the Promises and Challenges of Mandatory Arbitration for China? - Ji, Xueliang (Oregon Review of International Law, 2020)
Through comparing dispute resolution methods under bilateral investment treaties (BITs) and bilateral tax treaties, this Article critically discusses the advantages of incorporating mandatory arbitration in bilateral tax treaties and demonstrates that national sovereignty will not be decreased by it. As a result, the Article argues that it would, in fact, be beneficial for China to adopt the mandatory arbitration method, which would further strengthen the global reform initiated by the OECD.
Keywords: China; Dispute resolution; International tax law

Reimagining the Framework for Resolving Intra-African Commercial Disputes in the Context of the African Continental Free Trade Area Agreement - Onyema, Emilia (World Trade Review, 2020)
This article examines the effectiveness of the framework for the resolution of intra-African cross-border commercial disputes, arising from the projected increase in intra-African trade in goods, services, and investments under the African Continental Free Trade Area. It examines the peculiar nature of intra-African trade and of the participating entities to provide the context to discuss the three major processes adopted in commercial dispute resolution (litigation, mediation, and arbitration) in Africa. It then argues for the promotion of arbitration as the dispute resolution process of choice for such disputes. It reimagined the framework for arbitration at the continental level and made two proposals targeted at the greater efficiency of the process: the designation of Regional Arbitration Centres across the African Union's eight recognized Regional Economic Communities, to administer such references; and the establishment of an African Commercial Court as a one-stop court for the enforcement or annulment of the final award.
Keywords: AfCFTA; Arbitrage; Arbitragem; Arbitration; Commercial dispute; Dispute Resolution; Litigation

Dos efeitos da falência sobre a arbitragem - Deccache, Antonio Carlos Fernandes (Universidade de São Paulo, 2020)
Esta tese analisa os efeitos da falência sobre a arbitragem. A falência constitui um regime complexo, formado por regras materiais e processuais, criado para lidar com o problema da insolvência empresarial. Tem natureza de execução coletiva, reunindo todos os credores do falido e todos os seus bens, que devem ser liquidados a fim de pagar os credores. Para a consecução dos seus objetivos, a decretação da falência opera efeitos diretos sobre a pessoa do devedor, seus bens, seus contratos e seus processos. O processo falimentar realiza-se mediante procedimento administrado pelo Poder Judiciário, centralizado, público, com a finalidade de lidar com os diversos interesses envolvidos. Diversamente, a arbitragem é meio privado de solução de controvérsias pelo qual partes capazes elegem um terceiro, da sua confiança, para resolver litígio versando sobre direitos patrimoniais disponíveis. Tem natureza jurisdicional e caracteriza-se por constituir alternativa privada, rápida, flexível e especializada de dirimir demandas que admitem transação. Seu procedimento tem natureza de processo de conhecimento, terminando com a prolação de sentença, e constitui processo descentralizado, privado, usualmente sigiloso, no qual as partes têm ampla liberdade para definir as regras materiais e processuais aplicáveis. Enquanto a falência constitui sistema que visa lidar com interesses de ordem pública -- sendo, portanto, controlado pelo Estado, centralizado, público e coletivo --, a arbitragem pauta-se na autonomia da vontade, na descentralização do sistema de resolução de litígios, lida com interesses privados e é usualmente sigilosa. Considerando as relevantes diferenças entre os dois institutos, questiona-se em que condições a falência e a arbitragem podem coexistir. O que se propõe neste trabalho é, portanto, analisar quais são os efeitos que a falência opera sobre a arbitragem e como esses efeitos impactam na convivência entre os dois institutos. Para tanto, este estudo organiza-se em duas partes: parte I, na qual são apresentadas noções introdutórias da falência e da arbitragem, que servem para assentar as premissas utilizadas na análise; e parte II, na qual são analisados os efeitos propriamente ditos da falência sobre a arbitragem. A parte I está dividida em dois capítulos, nos quais se trata, sucessivamente, da falência e da arbitragem. Já a parte II está dividida em três capítulos, nos quais se trata, sucessivamente: (i) dos efeitos da falência sobre a convenção de arbitragem; (ii) dos efeitos da falência sobre o procedimento arbitral; e (iii) dos efeitos da falência sobre a sentença arbitral. Ao final, conclui-se que, apesar de a falência operar efeitos sobre alguns aspectos da arbitragem, impondo-lhe limites no contexto falimentar, isso não as torna incompatíveis. Aduz-se que a falência não invalida a convenção arbitral celebrada antes da falência, nem impede sua celebração pelo administrador, que, entretanto, depende de autorização judicial. Comprovase, também, que o advento da falência não atrai nem suspende os procedimentos arbitrais, mas impõe condições para que o processo possa se desenvolver. Por fim, evidencia-se que a sentença arbitral, uma vez proferida, deve ser submetida a verificação no processo falimentar.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration Agreement; Arbitration Award; Arbitration Proceeding; Bankruptcy; Direito falimentar; Falência; Insolvency; Juízo arbitral; Procedimento especial

The Applicability of Mediation as an Alternative Dispute Resolution Mechanism under OHADA Law - Leinyuy, Kifemmabuh Antonia (Scholars International Journal of Law Crime and Justice, 2020)
Almost 20 years after it adopted the Uniform Act on Arbitration, OHADA revised its Uniform Act on Arbitration and adopted a new Uniform Act on Mediation along with the fresh set of arbitration rules of the Common Court of Justice and Arbitration in Abidjan. These three texts were revised with the assistance of consultants. Among other changes, with the 2018 Uniform Act on Mediation, a solid platform for the use of mediation in the region is now in place. The ability of mediators to carry out their adjudication function with judicial intervention remains a major challenge by parties under the OHADA zones. In this light, the worry which this article seeks to uncover is how the new mediation law is applicable and facilitates the amicable settlement of investment disputes. The article also highlights the legal basis regulating the mediation process as a whole. In attaining these objectives, we employ doctrinal research methodology. The article conclude with vigorous recommendations which if effectively implemented will go a long way to enhance business (investment) security.
Keywords: ADR; Alternative dispute resolution; Applicability; Dispute resolution mechanism; MARD; Mediación; Mediation; Mediação; Médiation; OHADA Uniform Act

Letztwillige Schiedsverfügungen : Geltungsgrund und Geltungsgrenzen - Gleim, Jakob (Studien zum ausländischen und internationalen Privatrecht, 2020)
Nach §1066 ZPO gelten die Vorschriften über vertraglich vereinbarte Schiedsgerichte entsprechend für "Schiedsgerichte, die in gesetzlich statthafter Weise durch letztwillige [...] Verfügungen angeordnet werden". Während solche letztwilligen Schiedsverfügungen im 20.Jahrhundert sehr selten waren, beschäftigen sie heute die deutschen Gerichte mit gewisser Regelmäßigkeit. Mit Zunahme der praktischen Relevanz rücken auch die dogmatischen Grundlagen letztwilliger Schiedsverfügungen in den Fokus: Warum darf der Erblasser nicht nur materielle, sondern auch prozessuale Verfügungen von Todes wegen treffen? Wie weit reicht die Zuständigkeit des letztwillig eingesetzten Schiedsgerichts? Und welches Recht ist anzuwenden, wenn der Erbfall grenzüberschreitende Bezüge aufweist? Jakob Gleim beantwortet diese Fragen und bezieht dabei im Rahmen eines Rechtsvergleichs auch das US-amerikanische Recht ein. Fürdie vorliegende Dissertation wurde Jakob Gleim mit der2020 der Max-Planck-Gesellschaft ausgezeichnet. Is it possible for the testator to mandate unilaterally that all disputes concerning the estate are to be arbitrated instead of litigated? While such a testamentary arbitration clause is an expression of the decedent’s freedom of disposition, it contradicts the beneficiaries’ right of access to a public court. In his dissertation, Jakob Gleim examines the tension between the decedent’s freedom of disposition and the rights of the beneficiaries, balancing these two positions against one another and thereby identifying the reasons and the limitations of the validity of testamentary arbitration clauses. While such clauses were rather rare in the 20th century, German courts have to deal with them more regularly nowadays. In his dissertation, Gleim explores the practical significance of testamentary arbitration clauses as well as their advantages and disadvantages. The author also addresses the questions of how far the jurisdiction of the arbitral tribunal extends and which law is to be applied in cross-border cases. The inquiry also includes insights gained from a comparative analysis of US-American law.
Keywords: Arbitaje; Arbitrage; Arbitragem; Arbitration; Arbitration clause; Bankruptcy; Clause d'arbitrage; Insolvency; Mediation; Negotiation

The Standards for Proving Damages and Its Amount: A Comparative Study under Transnational Instruments and International Arbitration Awards - Shoarian, Ebrahim; Sahebjam, Sara (Public Law Researsh, 2020)
Defining the applicable standards for proving and measurement of damages constitute one of the most significant issues under the law of damages. In principle, an aggrieved party, who claims compensation for damages based on contractual liability is responsible for showing the existence and the amount of losses suffered or to be suffered. Due to great importance of the issue, transnational instruments of contract law, such as UNIDROIT Principles of International Commercial Contracts (UPICC), Principles of European Contract Law (PECL) and Draft Common Frame of Reference (DCFR) have set out, explicitly or implicitly, special standards such as reasonable certainty, reasonably likely to occur and so on for proving damages; By contrast, the Iranian laws and regulations including the Civil Code do not set out such standards. The legal scholarship and jurisprudence have also failed to address the issue. Therefore, a comparative study of the issue with particular look at international instruments and arbitral awards could provide a reliable source of guidance. This paper analyzes the general and specific standards for proving damages and those situations that fall outside of ambit of the standards such as late payment damages. By doing so, the paper tries to open the debate in Iranian law. یکی از موضوعات قابل توجه در حوزه حقوق خسارت، تعیین استانداردهای قابل اعمال برای اثبات خسارات و میزان آنها است. علی القاعده، زیان‌دیدهای که به استناد مسئولیت قراردادی برای مطالبه خسارت اقامه دعوی میکند، بایستی اصل و میزان خسارتی را که متحمل شده یا خواهد شد، به اثبات برساند. نظر به اهمیت موضوع، اسناد فراملی مربوط به حقوق قراردادها از جمله اصول قراردادهای تجاری بینالمللی، اصول حقوق قراردادهای اروپا و پیشنویس طرح مشترک مرجع، به صورت صریح یا ضمنی، استانداردهای مشخصی مانند قطعیت متعارف، وقوع محتمل متعارف و غیره را برای اثبات خسارت پیشبینی کردهاند. در مقابل، مقررات موضوعه ایران از جمله قانون مدنی؛ چنین استانداردهایی را تنظیم ننموده و موضوع نیز مورد بررسی حقوقدانان و رویه قضایی قرار نگرفته است. بنابراین، مطالعه تطبیقی موضوع با نگاهی ویژه بر اسناد بینالمللی و آرای داوری می‌تواند منبع قابل اتکایی برای طرح بحث باشد. این مقاله، استانداردهای عام و خاص اثبات اصل خسارت و میزان آن و نیز مواردی مثل خسارت تأخیر تأدیه را که خارج از قلمرو شمول این استانداردها هستند، مورد تحلیل قرار میدهد و در نهایت تلاش دارد تا باب بحث را در حقوق ایران بگشاید.
Keywords: Arbitral Awards; Reasonable Certainty; Reasonably Likely to Occur; Standard for Proving Damages; Transnational Instruments; آرای داوری; استاندارد اثبات خسارت; اسناد فراملی; قطعیت متعارف; وقوع محتمل متعارف

Fall of Last Safeguard in Global Dejudicialization: The Problem of Protecting Public Policy in Private Business Disputes - Ghodoosi, Farshad (Oregon Review of International Law, 2020)
The importance of courts is shrinking. This is largely due to global dejudicialization: the process of outsourcing disputes to private dispute resolution. In the last several decades, along with the triumph of neoliberalism, privatization of the resolution of disputes has become the gospel of modern judiciaries. Courts have been pushed to the tail end of the private adjudication process and are used only as the last resort. The courts’ warm embrace of this structure along with practitioners’ push has led to a staggering expansion of private dispute resolution. The world therefore has witnessed an unprecedented growth of arbitration—the primary mode of private dispute resolution.
Keywords: Business law; Dejudicialization; Dispute resolution; Déjudiciarisation; Privatization; Public policy

La protection des secrets commerciaux dans l'arbitrage commercial international - Bitho, Théodore-Alexandre de Nika (Université Paris 1, 2020)
L'importance des secrets d'affaires dans l'essor de l'économie mondiale n'est plus à démontrer. Ils sont, selon les indicateurs les plus fiables, la partie la plus importante du patrimoine des sociétés qui détiennent les plus grandes fortunes du monde. Mais force est de constater que leur protection dans l'arbitrage commercial international est peu effective. Ils sont victimes de divulgations licites ou illicites qui les exposent. Pour une meilleure protection des secrets d'affaires durant une procédure arbitrale, des mesures correctives sont nécessaires. Ces mesures doivent concourir à redéfinir un cadre juridique pratique dont le fondement et la justification est la protection de l'information qui a une valeur commerciale et économique. Pour ce vaste chantier, la contribution des usagers et praticiens de l'arbitrage commercial international est indéniable mais celle des États est indispensable.
Keywords: Arbitrage; Arbitrage commercial international; Arbitrage international; Arbitragem; Arbitration; Confidentiality; Confidentialité; Discovery; Droit commercial (droit international); International Arbitration; Preuve (administration); Protection des secrets; Protection of secrets; Rôle de l'arbitre; Secret commercial; Secret d'affaires; Secrets d'entreprises; Trade secret

Investor-state arbitration and African states: a proposal for a Pan-African investment court - Ama, Obiajunwa (Canterbury Christ Church University, 2020)
This thesis proposed for the reform of Africa’s Investor-State Dispute Settlement (ISDS) landscape through the establishment of a Pan-African Investment Court (PAIC) as a mechanism for the resolution of Investor-State Disputes. This proposal is influenced by the findings of my investigation on the functioning of Investor-State Dispute Settlement (ISDS) through the deployment of Investor-State Arbitration to resolve Investor-State Disputes between African states and foreign investors. This research is motivated by the criticisms of the Arbitration mechanism by a broad spectrum of constituencies within international investment law. These criticisms are primarily anchored on the legitimacy crises of ISDS, a dissatisfactory notion that denounces the deployment of the private mechanism and privity of contract ingrained investment arbitration framework to resolve publicly-inclined investor-state disputes. Ancillary to this critical holy grail are further dissatisfactions on the practical functionality of investment arbitration in aspects of high volume of cases against developing states, lack of diversity in the appointment of arbitrators and curtailment of sovereignty of host states through the intrusion of provisions of International Investment Agreements on legitimate internal decision-making powers. Consequently, this thesis investigated the practical functioning of ISDS in African states. After the study of the experiences of Egypt, South Africa and Tanzania; it was found that the legitimacy crises of ISDS also impacts on African states, and does not support their socio-economic and sustainable developmental aspirations. As a remedy, I proposed for a reform to an Investment Court System (ICS) through the establishment of a Pan-African Investment Court (PAIC). An evaluation of this recommendation was conducted that evidenced potential challenges that may mitigate its feasibility, thus leading to the advancement of two secondary reform alternatives vis the reform and retention of the current investor-state arbitration framework and engagement in innovative treaty-making practices by African states. To the best of my knowledge, this thesis has not been previously submitted in any higher institution or published by another person. The contents of this thesis are my ideas. Where the materials of others were used, due acknowledgement and reference was provided. Acknowledgements
Keywords: Arbitration; Investment Court System; Investments; Investor-State Dispute Settlement; Investor-state arbitration

Les suites de l’accord amiable en afrique - Blanc, Gérard (L'accord amiable, 2020)

Guide de l'arbitrage de l'OMPI - Centre d’arbitrage et de médiation de l'OMPI (OMPI, 2020)

L’exécution forcée des décisions de la Cour commune de justice et d’arbitrage et des sentences arbitrales impliquant le droit de l’OHADA - Kangambega, Élisabeth L. (Revue Burkinabè de Droit, 2020)

The regulation of international commercial arbitrators - Loreto Ilhao Moreira, João (University of Oxford, 2020)
International commercial arbitration has established itself as the main dispute resolution mechanism for international commercial disputes. This increased visibility has drawn attention to arbitrators’ public role, leading to a well-established general perception that arbitrators are bound to special obligations, such as the duty to be independent and impartial or the obligation to assure that arbitral proceedings are not abused to achieve nefarious goals. Despite this general acknowledgement, little attention has been paid to the mechanisms that ensure that arbitrators adhere to these obligations. In particular, there has been limited analysis of the underlying mechanisms that incentivise the production and enforcement of professional norms in this field. This thesis argues that the particulars of the arbitration market largely explains why the evolution of the regulation of international arbitrators has not matched those of other professions. At the same time, it will argue that those same particularities create incentives for several actors, most notably the arbitral community itself, to step in and occupy this regulatory vacuum. In particular, it explores the notion that the market strategies employed by arbitrators, arbitral institutions and other members of the arbitral community have the production of professional norms as a by-product. It further explores how the arbitral market tends to create an environment where compliance with professional norms is rewarded, leading, at the same time, the arbitral community to work as a network that promotes adherence to professional norms through mostly informal sanctions.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration (international law); Arbitration market; Dispute Resolution; International commercial arbitrators; Regulation

Arbitration related lessons: Insights from the supreme courts around the world - Nigmatullina, Dilyara; Vanlerberghe, Beatrix (b-Arbitra : Belgisch tijdschrift voor arbitrage, 2020)
In international arbitration, arbitrators have procedural powers that allow them to manage and conduct the arbitration proceedings in a fair and efficient manner. These powers are typically set out in the arbitration rules that the parties have agreed to, such as the International Chamber of Commerce (ICC) rules or the United Nations Commission on International Trade Law (UNCITRAL) rules. Arbitrators have the authority to determine the procedure to be followed in the arbitration, including the admissibility, relevance, materiality, and weight of the evidence presented. They can also decide on the language to be used in the arbitration and the location of the hearings. In addition, arbitrators can issue orders and directions as needed to ensure the fair and efficient conduct of the proceedings. This may include ordering the production of documents or witness testimony, or setting time limits for the submission of evidence. The present paper critically examines the lex arbitri, the law that governs the arbitral proceedings, and makes out a case that lex arbitri cannot be challenged in court, as the parties to the arbitration have agreed to resolve their disputes through arbitration rather than through the courts. However, if the tribunal exceeds its powers or acts in a manner that is inconsistent with the lex arbitri, the parties may have grounds to challenge the tribunal's decision on the grounds of lack of jurisdiction or due process. The paper summarises some key judgments in which Courts have upheld or quashed the Tribunals procedural orders. It will be concluded that the procedural powers of arbitrators in international arbitration are real and not perfunctory, though bounded within powers extended by Parties to the arbitral tribunal.
Keywords: Arbitrage; Arbitragem; Arbitration

Milletlerarası ticari tahkimde usule ilişkin konularda irade serbestisi - Takavut, İbrahim Doğan (İstanbul Üniversitesi, 2020)
Party autonomy is a well-accepted doctrine codified by national, international and supranational organizations that enables parties to be able to not only shape their contract but also their dispute resolution methods. It is believed that parties know their best interests; therefore, it is reasonable to give parties the freedom to decide whom they contract with and on what terms. This maximizes the autonomous freedom of the parties. Therefore, today it is well accepted that parties could waive their right to go to court and choose arbitration instead. However, through history, party autonomy has been seen as a direct threat to sovereign authority. States were always suspicious that arbitration hearings may not be as fair as court hearings since parties have the right to manipulate the arbitration processes. As a direct result of this, states regulated restrictions on party autonomy in international commercial arbitrations. Unfortunately, there is not an accepted definition of these restrictions and their effects on party autonomy have not been established or regulated internationally. Since party autonomy is the backbone of international commercial arbitration, it is important to crystalize the restrictions on party autonomy in procedural issues which directly affects the wellbeing of the arbitration process. Well accepted international regulations such as the New York Convention on Recognition and Enforcement of Foreign Arbitral Awards or UNCITRAL Model Law on International Commercial Arbitration helped to establish a unified system of restrictions on party autonomy but every state and state's courts interpret these restrictions differently. As procedural issues affect the result of international commercial arbitration, restrictions on party autonomy in procedural issues should be examined carefully. It is not an exaggeration that in international commercial arbitration the real and complicated questions most of the time originate from the issues of the boundaries of party autonomy. The tension between the party autonomy and efficiency of an arbitration process affects every decision which can be made by parties, arbitrators or courts. Therefore, this dissertation will investigate these problems in three parts by outlining; the source of party autonomy, the restrictions of party autonomy and the applications of these restrictions to party autonomy in procedural issues in international commercial arbitration. In the first part, the origin of party autonomy doctrine and how the doctrine developed throughout time will be examined. The law of arbitration, lex arbitri will be examined first. There are two accepted theories to determine lex arbitri. According to the territorialism theory, arbitration gets its power from the law of the place where the arbitration takes place. This theory suggests that the place where the arbitration takes place has control power over the procedure of arbitration. On the other hand, delocalization theory suggests that arbitral tribunals are detached from and not under the control of the law of the seat of arbitration. Although it looks like delocalization theory suits the needs of the international trade practice better because it assumes that arbitration is not in control of any law, it is still important to accept the power of the seat of arbitration since arbitration always needs a law to be controlled and get help. This section will also cover how different countries and international regulations determine lex arbitri and how it is determined in Turkish law according to the Turkish International Arbitration Law, Law no.4686. In the second part, restrictive measures of party autonomy will be examined. It will start with why party autonomy in procedural issues is needed to be restricted. Then the source of these restrictions will be mentioned. Afterwards, the common notions of the restrictions will be examined under the concepts of principles and rules. Under principles, the public policy and the common due process issues such as party equality, right to be heard, independence and impartiality of arbitrators will be examined in great detail. Then, mandatory rules which are based on these principles and their effect on party autonomy will be explained. The section will be closed with the examination of the circumstances where these principles and rules contradict each other. The main purpose of the second part is to look for commonly accepted problems of restrictions of party autonomy in procedural issues and how these common problems may evolve to a uniformed standard of the law, namely lex proceduralia. In the third part, the application of restrictions on party autonomy will be examined. The application of restrictions has different effects on parties, arbitrators and courts. Parties' autonomy is restricted while they are preparing their agreement on procedural issues, arbitrators are restricted during the arbitration processes and courts are restricted while helping the arbitration or controlling the awards. Before the arbitration process is initiated, parties' autonomy to shape their agreement looks like it is almost unlimited. However, parties' autonomy is always restricted by their choices. This situation is called the autonomy paradox. Therefore, the question of what parties can decide before the arbitrators join the processes is of the upmost importance. When the process starts and arbitrators start working, they balance the choice of parties and the restrictions of party autonomy. Since it is accepted that arbitrators are bound by the parties' choice and their power comes from the agreement of parties, it should be questioned whether they need to execute every choice of parties even if the choice is against mandatory provisions of lex arbitri or general accepted due process norms. Last but not least, courts' role on determining the party autonomy will be questioned. The power of courts to intervene in the arbitral process determine the practical limits of the autonomy of parties. During the arbitration process, the court may intervene in the process to help or control the arbitration; but real control power comes from when one of the parties asks courts to set aside or enforce the arbitral awards. While courts examine the arbitral awards, they also indirectly decide the limits of party autonomy. Therefore, this section will examine, which restrictions will affect the fate of the arbitral awards and how the courts should evaluate these restrictions. In conclusion, the dissertation will mainly investigate the topic of freedom of parties to determine the procedural issues in international commercial arbitration. It will aim to interpret and make use of the party autonomy doctrine as coherent as it can in the modern age. By illustrating the definition and limitations of the party autonomy in the procedural issues in international commercial arbitration, the dissertation will try to find a common international ground. This common ground may help to keep arbitration processes efficient while it provides fair hearings.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration boards; Commercial Arbitration; Commercial law; Free will; Hakem usulu; International Arbitiation Law; International Chamber of Commerce; Milletlerarası Tahkim Kanunu; Party autonomy; Procedural law; Tahkim; Tahkim kurulları; Ticaret hukuku; Uluslararası Ticaret Odası; Usul hukuku; Özgür istenç; İrade muhtariyeti

The Use of Mediation in ISDS - UNCITRAL Working Group III Virtual Pre-Intersessional Meeting (Asian Academy of International Law Limited, 2020)
Keywords: ISDS; Investor-State Dispute Settlement; Mediation; Médiation

La regulación del convenio arbitral y su implicancia en la institucionalidad del arbitraje comercial en el Perú - Vidal Ramos, Roger Pavletich (Universidad Nacional Mayor de San Marcos, 2020)
Estudia la regulación y los aspectos vulnerables del convenio arbitral, con énfasis a la necesidad de alcanzar una mejor institucionalidad del arbitraje comercial en el Perú. Determina los principios que fundamentan el arbitraje comercial. Identificar los supuestos de afectación al convenio arbitral. Analiza diversas sentencias de anulación de laudo respecto a la inexistencia de convenio arbitral. Analiza los diversos estudios teóricos y normativos en sede nacional e internacional respecto a los alcances del convenio y práctica arbitral. Identifica las instituciones jurídicas que brinden una protección del convenio en vía arbitral y judicial..
Keywords: Arbitrage; Arbitragem; Arbitraje industrial; Arbitraje y laudo; Arbitration; Convenios de arbitraje comercial; Convention d'arbitrage

The adaptation of China’s maritime arbitration system to international legal norms and practice - Xuan, Yan (The University of Queensland, 2020)
Maritime transport is essential to the world’s economy and maritime arbitration plays a crucial role in maritime dispute resolution. Nowadays, many coastal jurisdictions have set up their own maritime arbitration institutions such as those in the US, the UK, Germany, Australia, China, Japan, Hong Kong, and Singapore. Building a national world-advanced maritime arbitration system as soon as possible to suit China’s rapid developments in shipping and international trading does not permit of any delay. How should China improve her laws, rules and institutions, including those for the enforcement of maritime arbitration awards, having regard to leading international maritime arbitration systems? It is posited that selective adaptation from the successful experience of other maritime arbitration systems is the most convenient and effective way to achieve such a goal. This adaptation will follow from a comprehensive and comparative study of the maritime arbitration laws, rules and the maritime arbitration institutions, including the laws relating to the enforcement of maritime arbitration awards, from these main global maritime arbitration centres in order to make China’s maritime arbitration more competitive at the international level. This thesis does not purport to cover every research field relating to maritime arbitration. Instead, as previously stated, it will focus only on the comparative study of some selected key issues of international commercial arbitration among the selected jurisdictions. A comprehensive study of international commercial arbitration or international maritime law is not the subject of this thesis. It should be noted further that this research basically concentrates on the practical problems of maritime arbitration practices, rather than taking an overly theoretical approach. The thesis selects the UK, the US, Singapore and Hong Kong as the target jurisdictions for comparison. Through selective comparative analysis of the key issues of maritime arbitration systems in the selected jurisdictions, which are internationally recognised as significant by many arbitration scholars, this thesis proposes that all these issues could conveniently be categorised into four key criteria; namely, fairness, confidentiality, efficiency and enforceability. It follows that the adaptations of the Chinese maritime arbitration system should mainly focus on these four criteria, as these are the most critical factors for the development of Chinese maritime arbitration system. Moreover, these four criteria should also have significance for other underdeveloped maritime arbitration systems. Also, based on these four key criteria, the thesis provides some specific suggestions on how the Chinese maritime arbitration system can be adapted to reflect other selected jurisdictions in the respects of some key issues of international commercial arbitration.
Keywords: Arbitrage; Arbitragem; Arbitration; Confidentiality; Droit maritime; Efficiency; Enforceability; Fairness; Maritime arbitration

The enforceability of interim measures granted by an emergency arbitrator in international commercial arbitration - Zhang, Junmin (ProefschriftMaken, 2020)
The emergency arbitrator mechanism makes interim measures possible for parties involved in international commercial arbitration before the constitution of arbitral tribunals under urgent situations. However, with the development of the emergency arbitrator mechanism, the enforceability of interim measures made by an emergency arbitrator is questioned. This uncertainty leads to the hesitation of legal practitioners to apply the emergency arbitrator mechanism in practice. The research conducted two comparisons between different arbitration rules and between arbitration laws in jurisdictions. After discussing the legal status of an emergency arbitrator, the legal criteria to render interim measures, the potential barriers for the enforceability, and possible harmonization, it concluded that the interim measures granted by an emergency arbitrator in international commercial arbitration should be enforced and even harmonized through mandatory and non-mandatory methods.
Keywords: Arbitrage; Arbitragem; Arbitral Tribunal; Arbitration; Arbitration Law; Arbitrator; Commercial Arbitration; Emergency arbitrator; Enforceability; Interim measures; International commercial arbitration

基于国际商会仲裁规则下的国际工程项目仲裁管理 - 侯, 进才 (Journal of Oil and Gas Technology, 2020)
随着世界经济全球化，国内外企业之间的商贸往来迅猛发展，出现商事争议与纠纷的案件也呈现上升趋势，仲裁以其高效、快速等优点成为解决国际商事纠纷的最终方式之一。本文从仲裁的优点入手，首先阐述了完整仲裁过程中各个关键环节及注意事项，然后用流程图和横道图两种形式体现了一个完整的仲裁过程，最后就国际工程项目仲裁管理给出了具体建议。 With the globalization of the world economy, the commercial exchanges between domestic and foreign enterprises are developing rapidly, and the number of commercial disputes cases is growing quickly. Considering its advantages of high efficiency and speed, arbitration has become one of the final ways to solve international commercial disputes. This paper firstly presents the advantages of arbitration, then expounds the key stages and attention during the whole arbitration process. Flow chart and Gantt chart are drawn to show logics of the process. Specific suggestions on the arbitration management of international projects are given at the end of the article.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Arbitration Management; Arbitration Process; International Project; 仲裁程序; 仲裁管理; 国际工程